Making space for a case: an inquiry on the collaborative initiatives of selected public libraries in Metro Manila as points of access to justice - Castillo, Jan Francis O.; Silverio, Rochelle S. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2024)
Access to Justice is a vital concept extending beyond traditional legal institutions, encompassing various organizations that help individuals navigate legal complexities and access essential resources. Public libraries, as accessible community spaces, offer unique opportunities for collaboration on justice-related initiatives. This study investigates the collaborative efforts of public libraries in Metro Manila and their impact on Access to Justice. It examines library staff perceptions to provide recommendations for enhancing the role of libraries in promoting equitable Access to Justice within their communities.

The study used a qualitative approach with a focus on reflexive thematic analysis to investigate library staff practices and perceptions regarding strategies for championing Access to Justice. Results from semi-structured interviews were analyzed using Lave and Wenger’s Community of Practice (1996) and Mathiesen’s Informational Justice (2015).

The findings show that public libraries play a key role in the Community of Practice of Access to Justice by facilitating projects and bridging knowledge gaps in legal accessibility. Challenges include budgeting, lack of community awareness and engagement, and structural issues. Despite these challenges, public libraries remain optimistic about furthering the advocacy of making justice more accessible and have expressed recommended action steps for the future. The study recommends assisting public libraries by creating more findings from varied methodologies to formulate
relevant standards and insights that enhance their roles in Access to Justice.
Thesis
Keywords: Access to justice -- Philippines -- Metro Manila; Libraries and community -- Philippines -- Metro Manila; Public libraries -- Philippines -- Metro Manila